2016
DOI: 10.1590/1981-863720160002000073191
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative bone changes in TMJ assessed by cone beam computed tomography

Abstract: ObjectiveTo assess the degenerative bone changes of the jaw head and the condylar mobility regarding gender and age. Methods The sample was composed of 106 CBCT images for TMJ region from patients over 18 years old, from both genders, from the archives of a radiological clinic in the city RESUMO ObjetivoAvaliar as alterações ósseas degenerativas na cabeça da mandíbula e a mobilidade condilar com relação ao gênero e à faixa etária. MétodosA amostra foi constituída por 106 exames de TCFC para a região de ATM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In contrast, in the study of Cakur et al 21 and Melo et al 26 , erosion was the predominant finding in the mandibular condyle. The high prevalence of osteophyte and sclerosis in the current research may be related to the fact that the patients studied in this research had lower mean age relative to the previous studies 14,20 . Therefore, bone formation was more prevalent than bone deterioration.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In contrast, in the study of Cakur et al 21 and Melo et al 26 , erosion was the predominant finding in the mandibular condyle. The high prevalence of osteophyte and sclerosis in the current research may be related to the fact that the patients studied in this research had lower mean age relative to the previous studies 14,20 . Therefore, bone formation was more prevalent than bone deterioration.…”
Section: Discussionmentioning
confidence: 60%
“…There is controversy over the relationship between condylar bone density and degenerative bone changes in the TMJ. Some previous studies have not found a relationship between degenerative bone changes and bone density in people with TMD 2,14,20,21 . However, other investigations have shown lower bone density in patients with DJD 22,23 .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations